Acetylated cashew gum-based nanoparticles for the incorporation of alkaloid epiisopiloturine - do Amaral Rodrigues, Jessica; de Araújo, Alyne Rodrigues; Pitombeira, Nadia Aline; Plácido, Alexandra; de Almeida, Miguel Peixoto; Veras, Leiz Maria Costa; Delerue-Matos, Cristina; Lima, Filipe Camargo Dalmatti Alves; Neto, Augusto Batagin [UNESP]; de Paula, Regina Célia Monteiro; Feitosa, Judith Pessoa Andrade; Eaton, Peter; et al. (Elsevier, 2019)
The natural alkaloid epiisopiloturine has recently become the focus of study for various medicinal properties, particularly for its anti-inflammatory and antischistosomal effect. The incorporation of active molecules in natural polymeric matrices has garnered increasing interest during recent decades. A new derivative of cashew gum successfully obtained by gum acetylation has shown great potential as a carrier in controlled drug release systems. In this work, epiisopiloturine was encapsulated in acetylated cashew gum nanoparticles in order to increase solubility and allow slow release, whereas the morphology results were supported by computer simulations. The particles were produced under a variety of conditions, and thoroughly characterized using light scattering and microscopic techniques. The particles were spherical and highly stable in solution, and showed drug incorporation at high levels, up to 55% efficiency. Using a dialysis-based in vitro assay, these particles were shown to release the drug via a Fickian diffusion mechanism, leading to gradual drug release over approximately 6 h. These nanoparticles show potential for the use as drug delivery system, while studies on their potential anti-inflammatory action, as well as toxicity and efficacy assays would need to be performed in the future to confirm their suitability as drug delivery candidates.
Keywords: Acetic anhydride (PubChem CID: 7918); Acetone (PubChem CID: 180); Acetylation; Alkaloid; Cashew gum; Formamide (PubChem CID: 713); Hydrochloric acid (PubChem CID: 313); Pyridine (PubChem CID: 1049); Sodium hydroxide (PubChem CID: 14798)